Structural dynamics and societal impact of contractor-mediated interstate tribal labor migration in the Rarh region of India - Bapan Biswas; Kaushal Kumar Sharma; Bipul Biswas (Societal Impacts)
Migration serves as a crucial livelihood strategy for rural tribal populations facing limited economic opportunities, low wages, and agricultural instability. Contractors play a central role in facilitating this migration process, acting as intermediaries between laborers and employers. Through a multistage purposive sampling of 126 migrant households in the Rarh region of India, the research examines how contractors influence migration patterns, labor market outcomes, and social structures. The findings reveal that approximately 85 percent of migrants secure employment through a hierarchical contractor network comprising main contractors, professional sub-contractors, and micro-agent recruiters. This system creates structural dependency, as contractors provide advance payments that are later deducted from wages, reinforcing financial vulnerability. Migrants face significant challenges, including exploitative working conditions, wage suppression, and social marginalization due to language barriers and cultural displacement. Despite improving household income and living standards, contractor-driven migration perpetuates long-term economic entrapment and social dislocation. The study highlights the need for formal labor agreements, regulatory oversight of contractor practices, and enhanced social protections for migrant workers. By addressing these structural inequalities, policy interventions can promote fair labor practices and improve the resilience of migrant communities.